Web-based Cash Receipt and Disbursement Application at CV Banua Prima Teknik Banjarmasin - Monika Handayani; Muhammad Syahid Pebriadi; Fatimah Tri Maulida (International Journal of Economics, Commerce, and Management, 2024)
This research discusses the application of cash receipts and cash payments from cash sales and cash purchases at CV Banua Prima Teknik. This research aims to determine the accounting system for cash receipts and cash disbursements at CV Banua Prima Teknik, as well as to create a web-based cash receipt and disbursement application at CV Banua Prima Teknik. The theoretical framework of this research involves information system analysis, by examining the information needed by management, related functions, documents used, and document flowcharts. MySql is used as a database, with the PHP programming language. The research results show that the recording at CV Banua Prima Teknik has been computerized but still uses Microsoft Excel. The weakness of this method is that it is difficult to find out the recapitulation report of cash receipts and disbursements based on a certain period. Therefore, the application developed in this research is expected to help produce cash receipt and disbursement reports more effectively and efficiently, thereby improving performance in company financial management.